Consumption and savings in a low interest-rate environment - Simon Juul Hviid; Andreas Kuchler (Danmarks Nationalbank, 2017)
This paper studies consumption and savings decisions of Danish households before and during the financial crisis as well as in the more recent years characterized by negative policy rates. While all household groups decreased their consumption ratios immediately in response to the financial crisis, net savers have increased their consumption ratios to pre-crisis levels again. Net borrowers, in particular those with high gross debt, have increased their speed of consolidation further during recent years. This indicates that household balance-sheet adjustment is a relatively long process, which has extended into the beginning of the recent economic upturn. Further, we estimate the marginal propensity to consume (MPC) out of increasing housing wealth over one year to be around 4-6 per cent. Younger and more levered households have a larger MPC out of housing wealth, suggesting that collateral effects may play a role. The MPC is asymmetric; households adjust their consumption more in response to negative housing wealth shocks than to positive. Finally, we simulate an increase in interest rates at the household level, and find that the impact of the implied changes in liquidity on overall consumption is modest. However, the interest-rate sensitivity is considerably higher for at-risk groups, such as households with large debt and adjustable-rate mortgages. – – I papiret foretages en undersøgelse af danske husholdningers forbrugs- og opsparingsbeslutninger før og under finanskrisen samt i de senere års lavrentemiljø. Alle grupper af husholdninger reducerede deres forbrug umiddelbart efter finanskrisens begyndelse, men nettoopsparere har igen øget deres forbrugskvoter til et niveau svarende til før krisen. Omvendt har nettolåntagere, særligt dem med høj bruttogæld, øget konsolideringshastigheden yderligere over de senere år. Det indikerer, at ændringer i husholdningernes balancer er en længerevarende proces, som har strakt sig ind i begyndelsen af det seneste økonomiske opsving. Vi estimerer desuden den marginale forbrugstilbøjelighed ud af boligformuestigninger på en etårig horisont til 4-6 pct. Yngre og mere belånte husholdninger har en større marginal forbrugstilbøjelighed ud af boligformueændringer, hvilket kunne indikere, at mulighederne for sikkerhedsstillelse og belåning spiller en betydelig rolle for husholdningernes forbrugsbeslutninger. Den marginale forbrugstilbøjelighed er asymmetrisk. Husholdningernes forbrug reagerer kraftigere på negative stød til boligformuen end på positive. Endelig simulerer vi konsekvensen af en rentestigning for de enkelte husholdningers rentebetalinger, og finder herudfra en begrænset likviditetseffekt på det aggregerede forbrug. Forbrugets rentefølsomhed er dog betydeligt større for nogle grupper af husholdninger, såsom boligejere med høj gæld og variabelt forrentede lån.
Keywords: D12; D14; D31; D91; E21; 330; Households; Consumption; Low Interest Rates; Balance-Sheet Adjustment